2017
DOI: 10.1083/jcb.201605118
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-8 controls the secretion of inflammatory lysyl-tRNA synthetase in exosomes from cancer cells

Abstract: Lysyl-tRNA synthetase (KRS) can be released from cancer cells to cause inflammation, but the mechanism of KRS secretion is unknown. Kim et al. demonstrate that KRS is cleaved by caspase-8, which exposes a binding motif for syntenin and facilitates the secretion of KRS in exosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 52 publications
1
81
0
Order By: Relevance
“…Plasticembedded samples for immunostaining were sectioned using an ultramicrotome (60~80-nm thickness). Sections collected using an EM grid were stained for specific antigens using antibody-conjugated gold nanoparticles (immunogold labeling) (Kim et al, 2017). In HPF-FS images, we confirmed that the shape of exosomes was round.…”
Section: Cryofixation Of Exosome-treated Cells and Cryo-tem Of Exosomesmentioning
confidence: 56%
“…Plasticembedded samples for immunostaining were sectioned using an ultramicrotome (60~80-nm thickness). Sections collected using an EM grid were stained for specific antigens using antibody-conjugated gold nanoparticles (immunogold labeling) (Kim et al, 2017). In HPF-FS images, we confirmed that the shape of exosomes was round.…”
Section: Cryofixation Of Exosome-treated Cells and Cryo-tem Of Exosomesmentioning
confidence: 56%
“…Serum starvation of HCT116 colorectal carcinoma cells has been demonstrated to induce exosomal secretion of lysyl‐tRNA synthase (KRS) after dissociation of the multi‐tRNA synthetase complex . KRS sorting in exosomes was shown to involve caspase‐8 cleavage of KRS, thus unmasking a PDZ‐binding motif that could then interact with syntenin and Alix.…”
Section: Exosomes and Homeostasismentioning
confidence: 99%
“…In addition, patients with high KRS expression in cancer cells accompanied by low or no KRS expression in inflammatory cells had significantly reduced survival rates. Conspicuously, Kim et al 110 systematically studied the secretion mechanism of KRS in colorectal carcinoma cells (Fig. 4).…”
Section: Arss and Tumor Immunitymentioning
confidence: 99%